(untitled) (European Journal of Pure and Applied Mathematics, 2025)
Faithful matrix representations are presented for polynomially (p,q)-deformed Lie algebra l_p,q:[K₀,K₊]_p,q=rK₊, [K₋,K₀]_p,q=rK₋, [K₊,K₋]_p,q=P(K₀), where P is a real polynomial functions, p,q,r∈R^∗. The operators K₊,K₋ and K₀ satisfy certain physical properties. Conditions are set for F and the (p, q)-parameters, where the operators K+, K−, and K0, satisfy certain physical properties.